(untitled) (Research, Society and Development, 2024)
ADHD is a neurodevelopmental disorder affecting approximately 5% of children, with 1/3 maintaining normal functioning in adulthood. Symptoms include inattention, hyperactivity, and impulsivity. Diagnosis requires an interdisciplinary clinical approach. Educational strategies and behavioral interventions can improve academic and social performance, promoting inclusion. Research reviewed recent articles in Portuguese and English with descriptors related to ADHD, school, strategies, and teachers, using academic databases. Educators and peers must understand ADHD to reduce stigma and promote effective interventions. Strategies include symptom monitoring, teacher training, multidisciplinary support, family involvement, and specific classroom techniques. ADHD significantly impacts children’s academic performance and emotional well-being, requiring deep understanding from educators and healthcare professionals. Early interventions, such as classroom behavioral management strategies, are essential for effective management. Multidisciplinary treatment, including guidance for parents and teachers, is crucial. Overcoming stigma requires a collaborative and inclusive approach among all involved in the educational and mental health processes. The objective of the study is to investigate effective educational approaches for students with ADHD, aiming for inclusion and comprehensive progress, while providing practical guidance for educators.